2006
DOI: 10.1007/s10654-005-6031-3
|View full text |Cite
|
Sign up to set email alerts
|

Tension-type Headache in Adolescents and Adults: A Population Based Study of 33,764 Twins

Abstract: The aim of this study was to evaluate the 1-year-period prevalence of tension-type headache in a large population based sample. The study population included 33,764 twins aged 12-41 years old from the population based new Danish Twin Registry. They received a posted headache questionnaire and the response rate was 83.5%. The self-reported 1-year-period prevalence of tension-type headache was 86.0%; 78.9% among men and 92.5% among women. The 1-year-period prevalence of infrequent episodic, frequent episodic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 21 publications
3
75
3
8
Order By: Relevance
“…The restriction of the present data to 40 years old most likely causes the last-year prevalence of tension-type headache to be or be near peak values. The prevalence of frequent episodic and chronic tension-type headache was higher than in a previous Danish survey on twins [12]. The twins were from all of Denmark, while the present study was conducted in Copenhagen County, so it may reflect differences in rural and urban areas, but more likely it reflects a different age composition, i.e., the twins were age 12-41 years old.…”
Section: Methodological Considerationscontrasting
confidence: 62%
See 3 more Smart Citations
“…The restriction of the present data to 40 years old most likely causes the last-year prevalence of tension-type headache to be or be near peak values. The prevalence of frequent episodic and chronic tension-type headache was higher than in a previous Danish survey on twins [12]. The twins were from all of Denmark, while the present study was conducted in Copenhagen County, so it may reflect differences in rural and urban areas, but more likely it reflects a different age composition, i.e., the twins were age 12-41 years old.…”
Section: Methodological Considerationscontrasting
confidence: 62%
“…The observed agreement rate is 0.94 and Kappa is 0.87 (95% confidence limits: 0.85, 0.90), if the results from the two studies are combined [10,11]. The present and the previous survey were conducted in the same geographical area [10][11][12]. However, the validity of this method may change when applied to different populations.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, a cross-sectional twin study showed the prevalence of CTTH increased in adolescent girls beginning at age 15, whereas it remained unchanged in adolescent boys. 24 Whether sex hormones contribute to this phenomenon is unknown, and further investigation is warranted.…”
Section: Risk Factors For Incident Cdhmentioning
confidence: 99%